2011
DOI: 10.2174/157017911796117232
|View full text |Cite
|
Sign up to set email alerts
|

Activatable Optical Probes for the Detection of Enzymes

Abstract: The early detection of many human diseases is crucial if they are to be treated successfully. Therefore, the development of imaging techniques that can facilitate early detection of disease is of high importance. Changes in the levels of enzyme expression are known to occur in many diseases, making their accurate detection at low concentrations an area of considerable active research. Activatable fluorescent probes show immense promise in this area. If properly designed they should exhibit no signal until they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 324 publications
(207 reference statements)
1
41
0
Order By: Relevance
“…8 Originally developed for fluorescence imaging, the probes contained a fluorophore-quencher pair coupled to a peptide linker bearing an enzymatic site. 9 Upon cleavage of the linker, the pair is separated and fluorescence is restored.…”
Section: Activatable Probes For Molecular Imagingmentioning
confidence: 99%
“…8 Originally developed for fluorescence imaging, the probes contained a fluorophore-quencher pair coupled to a peptide linker bearing an enzymatic site. 9 Upon cleavage of the linker, the pair is separated and fluorescence is restored.…”
Section: Activatable Probes For Molecular Imagingmentioning
confidence: 99%
“…A large number of fluorescent dyes have been developed to detect enzyme activity during biochemical and in vitro assays. [7] Many of these dyes that are excited and/or emit in the red or near-infrared wavelength ranges have also been used for in vivo imaging, because these wavelength ranges have low absorbance in tissues. Bioluminescence has also been used to image in vivo enzyme activity using chemiluminescent substrates [8.9] and as reporter genes.…”
Section: Introductionmentioning
confidence: 99%
“…42 Dating back to the early 1950s, the coumarins of choice were the simple 4-methylumbelliferyl (4-MU) and resorufin derivatives, which were used as chemical probes for many different enzymes including esterases, phosphatases and glucosidases. [43][44][45] Furthermore, 6,7-dihydroxycoumarin serves as a colourimetric assay for bGlc due to enzymatic catalysed hydrolysis of the glycosidic linkage forming a brown-black complex in the presence of iron salts. 27 In 1954, Mead and co-workers reported that glucuronides of umbelliferone were practically non-fluorescent whereas the corresponding hydrolysis products, hydroxycoumarins, were highly fluorescent at pH 10-11 and therefore could be used to determine bGlc activity.…”
Section: Coumarinsmentioning
confidence: 99%